Gaya dan Pendekatan Kepimpinan Mohd Najib Abdul Razak:Satu Perspektif Kepimpinan - Khairil Annas, Jusoh (2011)
This thesis gives an overall view on the dynamics of Najib's leadership style and approach over the span of 33 years which covers his family background, education, politics and government administration. It will also emphasize on the important events based on the available facts beginning February 1976 until March 2009. The researcher also evaluated Najib's leadership orientation and inclination during that particular period in order to proof the effectiveness of his unique leadership style and approach which carries him up to the nation’s seat of power. When we refer to leaders, manifestly not much of accurate observations are made in the form of literature or writings. Most of the time, the writings are not academically oriented, roughly and vaguely grasped with no in-depth and based on assumptions which mislead the readers. Moreover, the leadership terms are not used in their correct and appropriate sense, meanings or contexts according to the theoretical definition of the leader. This research is carried out and written based on the leadership theories recognized by the prominent scholars in the field of management and leadership. In other words, it is not vaguely written without basis but founded on facts, references, academic findings and research on Najib. In addition, there is no in-depth research or academic analysis which is yet to be done on Najib's leadership style and approach.